Improvement of Methods for Evaluating the Cost-effectiveness of Energy Systems Projects - BURENINA, Irina Valereyvna; EVTUSHENKO, Evgenii Viktorovich; KOTOV, Dmitry Valeryevich; BATTALOVA, Alena Aleksandrovna; GAMILOVA, Dilyara Agelamovna (Journal of Environmental Management and Tourism, 2017)
Abstract : The relevance of the study stems from the need to find efficient project solutions for the development of energy systems based on alternative energy sources. For this task, it is necessary to identify trends in energy saving, availability of energy sources, constraints and risks associated with them, as well as to outline principles ensuring accurate account of all the factors determining the efficiency of energy systems in modern conditions. This article presents findings of the authors’ research on theoretical and practical issues of project management related to the creation of energy systems using renewable energy sources. The article considers methodological provisions that set approaches to the evaluation of the efficiency of energy systems projects. Besides, it proposes a model for estimating economic efficiency which takes into account specifics of prospects of a particular primary energy source. The authors studied renewable energy sources and determined the factors that are and will be important for their future use. The materials presented in this article are of practical value to scientists engaged in the assessment of the cost-effectiveness of projects for energy systems creation, as well as to large industrial complexes.